2001
DOI: 10.1136/gut.49.3.423
|View full text |Cite
|
Sign up to set email alerts
|

The natural course of hepatitis C virus infection after 22 years in a unique homogenous cohort: spontaneous viral clearance and chronic HCV infection

Abstract: The prevalence rates of mixed cryoglobulinaemia, sicca complex, positive thyroid autoantibodies, antinuclear antibody, rheumatoid factor, and antimitochondrial antibody in PCR positive women were 12.7%, 7.6%, 13.9%, 5.1%, 3.8%, and 3.8%. Conclusions-A benign course of HCV infection with lack of disease progression was observed in women with chronic HCV, 22 years after inoculation. Acute icteric hepatitis and the HLA DRB1*01 allele were associated with viral clearance. Despite this favourable outcome, high leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
105
1
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 51 publications
11
105
1
4
Order By: Relevance
“…The median fibrosis progression rate of 0.07 per year observed in this cohort was similar to or lower than reported in other studies of patients with chronic HCV-infection [16][17][18][19][20], but the progression rate was higher than in studies of young females who contracted an HCVinfection accidentally as a result of infected anti-D immunoglobulin in Ireland and Germany [5,21]. In a meta-analysis of the stage-specific fibrosis progression rate in different populations of HCV-patients, the mean progression rate among the IDUs were: F0-F1 0.116, F1-F2 0.085, F2-F3 0.085 and F3-F4 0.130 [20].…”
Section: Discussionsupporting
confidence: 81%
“…The median fibrosis progression rate of 0.07 per year observed in this cohort was similar to or lower than reported in other studies of patients with chronic HCV-infection [16][17][18][19][20], but the progression rate was higher than in studies of young females who contracted an HCVinfection accidentally as a result of infected anti-D immunoglobulin in Ireland and Germany [5,21]. In a meta-analysis of the stage-specific fibrosis progression rate in different populations of HCV-patients, the mean progression rate among the IDUs were: F0-F1 0.116, F1-F2 0.085, F2-F3 0.085 and F3-F4 0.130 [20].…”
Section: Discussionsupporting
confidence: 81%
“…In the Irish anti-D cohort, a 22-year follow-up study also showed mild fibrosis progression in affected women. 9 Third, we could not reliably evaluate alcohol consumption in our patients over this long observation period. However, we observed only a minority of patients with excessive alcohol consumption in our 25-year follow-up study.…”
Section: Discussionmentioning
confidence: 93%
“…8 Therefore the well-documented iatrogenic singlesource HCV outbreaks in recipients of HCVcontaminated anti-D immunoglobulin (Ig) in Ireland (1977Ireland ( -1978 and Germany (1978Germany ( -1979 provided valuable insight into the acute and chronic course of HCV infection in the past. [9][10][11][12] We have previously reported on the outcome of the German HCV (1b)-contaminated anti-D cohort at 20 and 25 years after infection and demonstrated a very low cirrhosis rate of only 0.5% in the overall cohort at 25 years after infection. 11,12 The aim of the present 35-year followup study was to reevaluate the liver disease progression in this unique cohort after another decade of data accrual in our prospective, community-based, multicenter study.…”
mentioning
confidence: 96%
“…Indeed, studies of women who were accidentally infected with the same inoculum (contaminated immunoglobulin D antibody) showed that despite receiving the same virus strain, viral diversity could not account for the dichotomy in outcome (clearance versus persistence). [29][30][31][32][33] Thus, differences in the host response were more likely to be the determining factor. Several important insights into this crossroad of viral and host genetics have been forthcoming from studies in human immunodeficiency virus (HIV) infection.…”
Section: Introductionmentioning
confidence: 99%